Analisis Semantik Leksikal pada Hapax Legomena dalam Buku Peradaban dan Kekecewaanya karya Sigmund Freud - Rizki Ziadah Akbar; Ade Siti Haryanti; Lulu Ur Rohmah (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to analyze the lexical meanings of Hapax Legomena found in the book Civilization and Its Discontents by Sigmund Freud, as well as to trace their semantic relations based on the Kamus Besar Bahasa Indonesia (KBBI) or the Great Dictionary of the Indonesian Language. Hapax Legomena refers to words that appear only once within a given text or corpus. These words are often marked by their expressive value, complex nuances of meaning, and stylistic function in constructing discourse. Therefore, this research considers Hapax Legomena as the central object of analysis to explore the semantic depth embedded in Sigmund Freud lexical choices. The study employs a descriptive qualitative approach through a literature-based analysis. Data were collected from the translated Indonesian version of Freud’s book, and the Hapax Legomena identified were then analyzed using lexical semantics, referencing definitions provided in the KBBI. Further analysis was conducted to examine their semantic relations, including synonymy (similarity of meaning), antonymy (opposition of meaning), and hypernymy (general-specific relationships). The findings reveal 96 Hapax Legomena that carry literal meanings traceable in the dictionary and exhibit semantic connections to other words within the text. These results indicate that, despite their singular occurrence, such words hold significant semantic value and contribute meaningfully to the richness of the discourse. Moreover, the analysis demonstrates the potential of lexical semantic approaches in enhancing the teaching and learning of the Indonesian language, particularly in areas such as contextual meaning interpretation, vocabulary enrichment, and appreciation of authorial style. Thus, this research contributes not only to theoretical linguistic studies but also offers practical implications for language education and therapeutic communication.